2022
DOI: 10.1002/14651858.cd014383.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic polypharmacy reduction versus polypharmacy continuation for people with schizophrenia

Abstract: Background In clinical practice, different antipsychotics can be combined in the treatment of people with schizophrenia (polypharmacy). This strategy can aim at increasing efficacy, but might also increase the adverse effects due to drug–drug interactions. Reducing polypharmacy by withdrawing one or more antipsychotics may reduce this problem, but must be done carefully, in order to maintain efficacy. Objectives To examine the effects and safety of reducing antipsychoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Conversely, our analysis highlights the critical need for a more cautious interpretation of APP benefits. While the results of Buhagiar et al [29], Kadra et al [61] and Bighelli et al [62] contribute to the complex discourse on antipsychotic treatments, our findings emphasize the necessity of a more rigorous evaluation before endorsing APP as simply an equivalent treatment modality compared to APM, suggesting that its potential risks may outweigh the perceived benefits in many cases. This stance is not only informed by our analysis of mortality risks but also by a broader consideration of patient safety and treatment efficacy [48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Conversely, our analysis highlights the critical need for a more cautious interpretation of APP benefits. While the results of Buhagiar et al [29], Kadra et al [61] and Bighelli et al [62] contribute to the complex discourse on antipsychotic treatments, our findings emphasize the necessity of a more rigorous evaluation before endorsing APP as simply an equivalent treatment modality compared to APM, suggesting that its potential risks may outweigh the perceived benefits in many cases. This stance is not only informed by our analysis of mortality risks but also by a broader consideration of patient safety and treatment efficacy [48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 53%
“…Bighelli et al (2022) in their meta-analysis compared antipsychotic polypharmacy (APP) reduction to persistence in schizophrenia, focusing on outcomes like hospitalization, side effects, and, notably, mortality. The results showed no significant differences between the two approaches [62]. Furthermore, the study observed that persistence with APP might be associated with a lower rate of participant discontinuation due to inefficacy, emphasizing the critical need for personalized treatment plans and further investigation into the complex effects of APP.…”
Section: Discussionmentioning
confidence: 81%
“…In the future the use of genetics beyond drug metabolism, but rather polygenic risk scores or epigenetic methylation analyses may prove fruitful for response prediction [55]. Regardless, many psychiatrists will move as the next step to the concept of polypharmacy and adding a second antipsychotic with perhaps a different receptor profile [56]. While some believe polypharmacy leads to reduced longevity overall, there is no evidence for that [57].…”
Section: The Beginningsmentioning
confidence: 99%
“…Polypharmacy, the concurrent use of multiple medications, is common and a complex issue in the treatment of schizophrenia ( Kishimoto et al, 2013 ; Bighelli et al, 2022 ). Polypharmacy in schizophrenia is often based on clinical experience rather than evidence-based practice.…”
Section: Introductionmentioning
confidence: 99%